PERANCANGAN DAN IMPLEMENTASI APLIKASI SISTEM INFORMASI PERPUSTAKAAN DENGAN MENGGUNAKAN METODOLOGI PENGEMBANGAN MODEL SEKUENSIAL LINIER - Ahmad Feriyanto Alulu (Jurnal Informatika, 2012)
This study aims to make software development documents more organized and have better quality in using of library information systems. The method used in this research is the study of literature and the literature by using the linear sequential model development methodology which is expected to be a reference in the design of library information system. The results showed that the Library Information System Applications using Linear Sequential Methodology is often called the Waterfall Methodology or waterfall is a model that proposes an approach to software developers a systematic and sequential. The core of this methodology is the construction of a system is done sequentially or linearly. If step one has not done it will not be able to do the next  step( two, three, and so on). automatically stages  3 will be made ​​if the first stage and the second was done. Its expected to make the design and construction documents to be organized and the quality of the resulting system will be better. Keywords: Sequential Linear, Library Information System.